Ozonização em grãos de amendoim com vagem e sem vagem e qualidade após armazenamento - Laureth, Jessica Cristina Urbanski (2019)
Peanuts (Arachis hypogaea L.) are susceptible to fungal contamination at all stages of their production chain, which can lead to the production of aflatoxins, toxic secondary compounds. In addition, it is rich in unsaturated fatty acids, which, depending on processing and storage conditions, may oxidize, influencing the postharvest quality of these grains. Among the technologies that seek to prolong food quality is ozone. Ozone acts against microorganisms, mycotoxins, pests and pesticides, in addition to influencing grain quality. However, it can cause oxidative damage, degrading organic constituents. Thus, the objective of this study was to verify the effect of ozone gas on the quality of peanut and poden peanut grains after application and an eight-month storage period. Fungus reduction and changes in lipid quality of peanut grain and oil after ozonization were evaluated (Article 1). To verify such changes, total fungal count, electrical conductivity, peroxide index and 2-thiobarbituric acid tests were performed. Physiological quality, physicochemical and fungal reduction of ozonated grains (Article 2) correlated to parameters water content, respiratory activity, electrical conductivity, total fungal count, texture, pH and color were also determined. In addition, the quality of peanut grains and crude oil was evaluated (Article 3) through acidity, lipid content, peroxide index, free fatty acids and iodine index. Ozone application was performed at concentrations of 10, 30, and 50 ppm, and 30, 45, and 60 minutes of gas exposure time, following a Central Composite Design. Ozone concentration and gas exposure time significantly influenced the fungal count. Maximum reductions were achieved using the 50 ppm concentration and 60 minutes exposure time. The electrical conductivity of the exudates was increased by ozone concentration, showing that the integrity of the cell membrane was affected by the gas. After eight months of storage, increased respiration and reduced pH of grains was possibly related to the variable. The respiratory rate of the organs increased when they were exposed to higher concentrations of ozone. The results also showed that there is depigmentation in the film, but this change is not determinant from a qualitative point of view. There was lipid degradation at the cellular level and the time of gas exposure reduced the lipid contents of ozonated grain samples. Ozone may have started the deterioration of the oil; however, the average values of peroxide and free fatty acids index were close to those recommended by Brazilian legislation. Ozone application has an effect on fungal reduction, electrical conductivity, and respiratory activity after the storage period. Ozonization can be applied to peanut grains, reducing fungal contamination, but exposure factors should be evaluated to avoid affecting the nutritional quality of the product.